Modified the RC4 Stream Cipher Algorithm Based on Irreducible Polynomial - Zainab Mohammed Hussein; Abdul Monem Saleh Rahma (Engineering and Technology Journal, 2015)
The increase in the speed of computers and adoption on it as means of encryption (send and receive encrypted data), which led to the development of modern encryption techniques such as (stream cipher and block cipher). This increase in speed of the computers has increased the strength of the attacking techniques for stream cipher which is built according to two ways: (random key generation and XOR operation). This paper proposes approach in modifying RC4 stream cipher algorithm based on irreducible polynomial which is used in modern encryption methods such as AES.The proposed algorithm achieves best results, it provides high level of complexity, to decrypt an encrypted message is composed of 8-bit the attacker needs 30*28 probability of keys at minimum, this mean the proposed algorithm will increase the complexity of the algorithm 30 times